2014
DOI: 10.1371/journal.pone.0109915
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Effectiveness on Prescribing of Two Multifaceted Educational Interventions: Results of Two Large Scale Randomized Cluster Trials

Abstract: IntroductionInformation on benefits and risks of drugs is a key element affecting doctors’ prescribing decisions. Outreach visits promoting independent information have proved moderately effective in changing prescribing behaviours.ObjectivesTesting the short and long-term effectiveness on general practitioners’ prescribing of small groups meetings led by pharmacists.MethodsTwo cluster open randomised controlled trials (RCTs) were carried out in a large scale NHS setting. Ad hoc prepared evidence based materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Others investigated three or more components. Sixteen studies out of the 21 included in this review used academic detailing (AD) as part of a multi-component intervention strategy [ 10 , 13 , 17 , 21 , 23 34 ]. Thirteen studies had a form of audit and feedback integrated into their intervention [ 17 – 19 , 22 25 , 28 , 29 , 32 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Others investigated three or more components. Sixteen studies out of the 21 included in this review used academic detailing (AD) as part of a multi-component intervention strategy [ 10 , 13 , 17 , 21 , 23 34 ]. Thirteen studies had a form of audit and feedback integrated into their intervention [ 17 – 19 , 22 25 , 28 , 29 , 32 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because the context of each study varied and there was not a uniform reporting measure of effect size, we measured the effectiveness of an intervention based on the p values of change between study arms reported in each study. Thirteen of the 21 studies reported a significant positive change ( p < .05) in their primary outcomes on the intervention arm [ 17 20 , 22 , 23 , 25 , 27 29 , 32 , 34 , 35 ]. All of these studies investigated the effects of multi-faceted interventions that included at least two of the intervention categories described under the data analysis section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational interventions have been shown to improve knowledge of pharmacovigilance (50) and prescribing competency (51) as well as to strengthen AMS (52)(53)(54), although the effects may be short-lived. Online learning as part of AMS programmes has been playing an increasing role (55) and online training of GPs has been shown to reduce antimicrobial prescribing for respiratory disease (56).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have showed effective interventions to modify prescribing habits [18, 19], in particular for NSAIDs [20]. A few other studies have tried to evaluate the efficacy of removing economic barriers to appropriate drug prescribing, but not specifically regarding paracetamol [12, 21].…”
Section: Discussionmentioning
confidence: 99%